A dress of violet taffeta eaudiobook - Arlen, Tessa (Penguin Audio, 2022)
A sumptuous novel based on the fascinating true story of La Belle Époque icon Lucy, Lady Duff Gordon, who shattered the boundaries of fashion with her magnificently sensual and enchantingly unique design from the USA Today bestselling author of In Royal Service to the Queen. Lucy Duff Gordon knows she is talented. She sees color, light, and texture in ways few people can begin to imagine. But is the male dominated world of haute couture, who would use her art for their own gain, ready for her? When she is deserted by her wealthy husband, Lucy is left penniless with an aging mother and her five-year-old daughter to support. Desperate to survive, Lucy turns to her one true talent to make a living. As a little girl, the dresses she made for her dolls were the envy of her group of playmates. Now, she uses her creative designs and her remarkable eye for color to take her place in the fashion world—failure is not an option.  Then, on a frigid night in 1912, Lucy’s life changes once more, when she becomes one of 706 people to survive the sinking of the Titanic. She could never have imagined the effects the disaster would have on her fashion label Lucile, her marriage to her second husband, and her legacy. But no matter what life throws at her, Lucy will live on as a trailblazing and innovative fashion icon, never letting go of what she worked so hard to earn. This is her story.